Research and Medical Transcranial Doppler System - LEWANDOWSKI, Marcin; WALCZAK, Mateusz; KARWAT, Piotr; WITEK, Beata; KARŁOWICZ, Paweł (Archives of Acoustics, 2016)
A new ultrasound digital transcranial Doppler system (digiTDS) is introduced. The digiTDS enables diagnosis of intracranial vessels which are rather difficult to penetrate for standard systems. The device can display a color map of flow velocities (in time-depth domain) and a spectrogram of a Doppler signal obtained at particular depth. The system offers a multigate processing which allows to display a number of spectrograms simultaneously and to reconstruct a flow velocity profile. The digital signal processing in digiTDS is partitioned between hardware and software parts. The hardware part (based on FPGA) executes a signal demodulation and reduces data stream. The software part (PC) performs the Doppler processing and display tasks. The hardware-software partitioning allowed to build a flexible Doppler platform at a relatively low cost. The digiTDS design fulfills all necessary medical standards being a new useful tool in the transcranial field as well as in heart velocimetry research.